Plan de negocios para la creación de una escuela de robótica para niños en el cantón Latacunga. - Salazar Zambrano, Estefania Isabel (2023)
Educational robotics in the last decade has been gaining an important space in the years of basic training since it helps to develop in students skills in the areas of mathematics, technology and science, at the same time it promotes logical thinking, teamwork and creativity in children. In this sense, the objective of this project is to develop a business plan for the creation of a robotics school for children in the Latacunga canton. Through market research that was carried out. Conducted in different educational institutions in the canton, it was learned that students between the ages of $15 and more are interested in creating video games, handling drones, and competitive robots than in other technological issues, which gave us an opportunity to complement this innate interest with practical classes in workshops where young people can manipulate tools, electronic parts, and computers, with the aim that they participate in technological development in their early years of training and in the future choose to study a career in engineering and science. thus contributing to the industrial and scientific development of the country.